2005
DOI: 10.1111/j.1365-2966.2005.09077.x
|View full text |Cite
|
Sign up to set email alerts
|

Models of class II methanol masers based on improved molecular data

Abstract: The class II masers of methanol are associated with the early stages of formation of high-mass stars. Modelling of these dense, dusty environments has demonstrated that pumping by infrared radiation can account for the observed masers. Collisions with other molecules in the ambient gas also play a significant role, but have not been well modelled in the past. Here we examine the effects on the maser models of newly available collision rate coefficients for methanol. The new collision data does not alter which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
339
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(382 citation statements)
references
References 38 publications
39
339
2
Order By: Relevance
“…Norris et al 1993;Moscadelli et al 2002). The physical conditions required to produce the 6.7-and 12.2-GHz methanol masers are similar, but do not cover exactly the same parameter space (Cragg, Sobolev & Godfrey 2005), making the combination of the two transitions especially useful. Furthermore, since 12.2-GHz methanol masers are almost always found to have lower flux densities than their 6.7-GHz counterparts and the fact that there have been no serendipitous detections of 12.2-GHz methanol masers without 6.7 GHz, a complete sample of 12.2-GHz methanol masers can be gained by targeting a complete sample of 6.7-GHz masers.…”
Section: Introductionmentioning
confidence: 93%
“…Norris et al 1993;Moscadelli et al 2002). The physical conditions required to produce the 6.7-and 12.2-GHz methanol masers are similar, but do not cover exactly the same parameter space (Cragg, Sobolev & Godfrey 2005), making the combination of the two transitions especially useful. Furthermore, since 12.2-GHz methanol masers are almost always found to have lower flux densities than their 6.7-GHz counterparts and the fact that there have been no serendipitous detections of 12.2-GHz methanol masers without 6.7 GHz, a complete sample of 12.2-GHz methanol masers can be gained by targeting a complete sample of 6.7-GHz masers.…”
Section: Introductionmentioning
confidence: 93%
“…3 caption for a general explanation of box plots. Cragg, Sobolev & Godfrey (2005) presented maser modelling of class II methanol masers and their figs 2 and 3 show how maser brightness varies with a number of parameters, including dust temperature, which shows a sharp increase in maser brightness at a higher dust temperature for 12.2-GHz methanol masers compared to 6.7-GHz methanol masers. Their findings are naively consistent with our results, showing that sources associated with both 6.7-and 12.2-GHz methanol masers have slightly warmer dust temperatures, however, there are a number of complex factors at play, including the fact that these parameter plots show how dust temperature varies as other parameters remain fixed, and the fact that our dust temperatures represent the average of a significant region.…”
Section: Comparison With Maser Modelsmentioning
confidence: 99%
“…The class II methanol masers are thought to be pumped by infrared radiation (Cragg et al 2005) and found to originate in accretion disks in highmass star-forming regions (Sanna et al 2010;Sugiyama et al 2014). The similarity in the variability found in the methanol maser emission (MME) and the IR variability may therefore represent the frequency of the infrared luminosity variations of the warm disk from accretion events, which is also responsible for pumping the class II MME (Cragg et al 2005). We searched for MME in the 13 VYSOs and did not find any methanol masers within a radius of 30″.…”
Section: Discussionmentioning
confidence: 99%